The Relationship Between Parenting Style, Development Stimulation, and Gross Motoric and Language Ability in Children Under Five - Wigati, Dhiyan Nany; Tamtomo, Didik; Retno Dewi, Yulia Lanti (Indonesian Journal of Medicine, 2016)
Background: Children progress through growth and development process according to age. Child growth and development are influenced by genetic and environmental factors during antenatal, intranatal, and postnatal periods. Child development is optimalized if there is social interaction that fulfill the need of the child at different stages of development. This study investigated the relationship between parenting style, development stimulation, and gross motoric and language ability in children under five in Grobogan, Central Java.Subjects and Method: This was an analytic observational study with cross sectional design. This study was conducted in Toroh I Health Center, Grobogan sub-district, Central Java, from ÃÂ September, 17 to October, 17 2016. A total sample of 100 mothers and their children aged 1-5 years were selected for this study by cluster sampling. The dependent variable was gross motoric and language ability. The independent variables were parenting style and development stimulation. Gross motoric and language ability was measured by Denver II. Parenting style and development stimulation were collected by a set of questionnaire. The data were analyzed by multiple logistic regression.Results: There were positive and statistically significant relationships between democratic parenting style (OR= 3.73; 95% CI=1.16 to 12.00; p=0.027), development stimulation (OR= 5.37; 95% CI=1.75 to 16.47; p= 0.003), and better gross motoric ability. There were positive and statistically significant relationships between democratic parenting style (OR= 3.50; 95% CI=1.18 to 10.35; p=0.023), development stimulation (OR= 3.49; 95% CI=1.24 to 9.84; p= 0.018), and better language ability.Conclusion: Democratic parenting style and development stimulation are associated with both better gross motoric ability and better language ability.Keywords: parenting style, development stimulation, gross motoric ability, language abilityCorrespondence:ÃÂ Dhiyan Nany Wigati. An-Nur Midwifery Academy, Purwodadi, Central Java. Email: dhiyanwigati@gmail.comIndonesian Journal of Medicine (2016), 1(3): 169-174https://doi.org/10.26911/theijmed.2016.01.03.04